2019
DOI: 10.1111/nan.12538
|View full text |Cite
|
Sign up to set email alerts
|

Review: PrP 106‐126 – 25 years after

Abstract: A quarter of a century ago, we proposed an innovative approach to study the pathogenesis of prion disease, one of the most intriguing biomedical problems that remains unresolved. The synthesis of a peptide homologous to residues 106‐126 of the human prion protein (PrP106‐126), a sequence present in the PrP amyloid protein of Gerstmann–Sträussler–Scheinker syndrome patients, provided a tractable tool for investigating the mechanisms of neurotoxicity. Together with several other discoveries at the beginning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 116 publications
2
16
0
Order By: Relevance
“…PrP 106-126 is widely used as a model for studying PrP Sc neurotoxicity because it leads to neuronal apoptosis and cytotoxicity [24][25][26]. In our study, Bax accumulation in and the release of cytochrome c from mitochondria were observed, while the expression of Bcl-2, an antiapoptotic factor, was decreased.…”
Section: Discussionmentioning
confidence: 48%
“…PrP 106-126 is widely used as a model for studying PrP Sc neurotoxicity because it leads to neuronal apoptosis and cytotoxicity [24][25][26]. In our study, Bax accumulation in and the release of cytochrome c from mitochondria were observed, while the expression of Bcl-2, an antiapoptotic factor, was decreased.…”
Section: Discussionmentioning
confidence: 48%
“…The prion peptide PrP106-126 has been widely used as a suitable model peptide because this fragment is soluble in water and exhibits several physicochemical and biological properties similar to those of PrP Sc , such as aggregation in solution, antiproteinase K digestion, and neurotoxicity [42,43]. However, an important argument about PrP peptide 106-126 is the facts that it is not actually a fragment found in the brains of humans or animals with prion diseases [44]. Even we investigated baicalein effect in this study, we will further study the issue using longer fragments or full-length PrP mutant models to examine therapeutic potential of baicalein in prion disease.…”
Section: Discussionmentioning
confidence: 99%
“…The amyloidogenic prion residues 106–126 [ 756 , 757 ] in the N-terminal domain are characterized by hydrophilic and hydrophobic regions that can increase lipid density and membrane viscosity upon embedding into lipid bilayers [ 758 ]. The prion peptide fragment 106–126 can form heterogenous single cation channels with different conductance and kinetic properties in lipid bilayers, modifying electrolyte homeostasis and affecting cellular functions [ 759 , 760 , 761 ] while the conversion of PrP C to PrP Sc is often associated with membrane abnormalities including decreased membrane fluidity [ 762 ].…”
Section: The Effects Of Melatonin On Lipid Phase Transition Lipid Com...mentioning
confidence: 99%